2020
DOI: 10.1111/jocn.15404
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic teams and nursing care: A critical incident study of nurses in the emergency medical service

Abstract: Aim and objectives The aim of the study was to describe Emergency Medical Services (EMS) nurses’ experiences of and coping with critical incidents, when providing nursing care as a member of a dyadic team. Background Nursing care in EMS is a complex task, taking into account the physical, psychological as well as existential dimensions of the patient's suffering. In this, EMS nurses are dependent on the dyadic team. Teams in EMS are described as essential for providing safe medical care. However, nursing care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
2
19
0
2
Order By: Relevance
“…As stated in the result, 'there are colleagues who, even when making their way out to a patient, decide that the patient should remain at home, regardless of the patient's wishes' (category 4, item 4), surrogate decision-making can be complicated. Holmberg et al (2020) found this to be especially challenging within the AS, relating to the colleague's lack of competence disrespectful approach and common goals. However, having a competent colleague, together with consensus regarding the goal of the care, promotes functional co-operation within the dyadic AC team.…”
Section: 6mentioning
confidence: 99%
“…As stated in the result, 'there are colleagues who, even when making their way out to a patient, decide that the patient should remain at home, regardless of the patient's wishes' (category 4, item 4), surrogate decision-making can be complicated. Holmberg et al (2020) found this to be especially challenging within the AS, relating to the colleague's lack of competence disrespectful approach and common goals. However, having a competent colleague, together with consensus regarding the goal of the care, promotes functional co-operation within the dyadic AC team.…”
Section: 6mentioning
confidence: 99%
“…A dysfunctional and confidence-lacking collegial team is described as a cause of worry in RNs, thus having a negative impact on caring (Svensson & Fridlund, 2008). This is confirmed in a recent study by Holmberg et al (2020) stressing the importance of reflections as a part of daily practice to develop both nursing care and to strengthen the dyadic team in EMS. The importance of communication relates to our findings of how RNs regain confidence in the situation using verbal and nonverbal communication with colleagues as well as patients.…”
Section: Results Discussionmentioning
confidence: 69%
“…Aside from own competence and experience, the RNs in this study emphasize the importance of being part of a well-functioning collegial team as a foundation for the caring approach in stressful situations while encountering patients with chest pain. The importance of a well-functional team was stressed while providing care in EMS (Holmberg et al, 2020;Patterson et al, 2011). A dysfunctional and confidence-lacking collegial team is described as a cause of worry in RNs, thus having a negative impact on caring (Svensson & Fridlund, 2008).…”
Section: Results Discussionmentioning
confidence: 99%
“…Ambulance personnel may consist of voluntary workers, firefighters, paramedics, nurses, or medical doctors [ 1 ]. Regardless of their formal titles, ambulance personnel need to assess, load, and move the patient safely and maintain a professional relationship with the patient and significant others [ 2 ]. In some countries, the duties of driving the ambulance and providing medical care are held by separate individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, the duties of driving the ambulance and providing medical care are held by separate individuals. In other settings, a team of individuals is trained to fulfil either role [ 2 ]. Despite how the service is organized, being the patient of an ambulance service entails being dependent on the caregivers and their competence through all phases of prehospital care, including the alarm call, the pick-up scene, the transportation process, and finally, the arrival and handover to the hospital or other destination.…”
Section: Introductionmentioning
confidence: 99%